Coupling of Fe-N-C single atom catalyst and ferrocene-modified graphitic carbon nitride as an efficient photocatalyst for removal of pollutants from water - Huang, Zhikun; Yu, Haojie; Wang, Li; Liu, Xiaowei; Ren, Shuning; Huang, Yudi; Gong, Xiaodan; Liang, Ruixue; Shen, Di; Wu, Xudong (Separation and purification technology, 2023)
[Display omitted] •The Fe-N-C content of FCF-A composites can be precisely controlled can be precisely.•Two main routes of BPA degradation pathway were investigated by DFT calculations.•The synthesized FCF-0.05 exhibited great potential for practical application. Graphitic carbon nitride (CN) is a promising photocatalyst in wastewater treatment field; however, CN suffers from sluggish photogenerated charge separation. Herein, a single atom catalyst (Fe-N-C) coupled with ferrocene-functionalized CN (CN-Fc) heterostructured composite (FCF-0.05) with superior photocatalytic activity was fabricated. Bisphenol A (BPA) can be removed completely over FCF-0.05/PMS/Vis system within 60 min, the corresponding apparent rate constant (k) was 24 times and 10 times higher than those of CN/Vis and CN/PMS/Vis systems, respectively, which was derived from the efficiently charge separation since generated interfacial heterojunction. Moreover, FCF-0.05/PMS/Vis system exhibited high stability and superior catalytic activity in real water and outdoor environment. Furthermore, the BPA degradation mechanism and pathway have been identified by combination experimental (quench testing, electron paramagnetic resonance and liquid chromatography-mass spectrometry techniques) and density functional theory (DFT) calculations method, providing insight of synthesis of cost-effective photocatalyst with outstanding catalytic activity.